Moderating effect of perceived organizational structure on perceived job uncertainty and affective commitment relationship - Uygur, Duygu (My University, 2005)
Name and Surname:Duygu Uygur Field:Business Administration Programme:Organizational Behavior Supervisor:Prof. Dr. Suna Tevrüz Degree Awarded and Date: Master- July 2005 Task Uncertainty, Organizational Structure, Mechanistic and Organic Systems, Affective Commitment

The study investigates the moderating effect of perceived organizational structure in the sense that mechanistic or organic tendency of the organization on perceived task uncertainty and affective commitment relationship. As the result of measurement instrument analysis, task uncertainty is represented by one factor that is analysis uncertainty. According to the results of the study, perceived organizational structure neither as a continuous variable nor as a categorical variable, which consists of mechanistic and organic categories, has no significant effect on analysis uncertainty and affective commitment relationship. However perceived analysis uncertainty and affective commitment relationship has been significantly affected by trust which is an organizational structure dimension. Trust lightened the negative effect of analysis uncertainty on affective commitment. Same finding was observed also in production department. R&D, sales-marketing and production departments were reordered in terms of perceived analysis uncertainty. Departments were ordered from highest uncertainty perception to lowest as sales-marketing, R&D and production. Perceived analysis uncertainty is negatively related with tenure and positively related with education and training. Employees who perceive less uncertainty are more committed to organization. All the findings mentioned above were discussed at the end of the study and a new model was drawn. Soyadı: Duygu Uygur zce İşletme Program:Örgütsel Davranış Prof. Dr. Suna Tevrüz Tez Türü ve Tarihi:Yüksek Lisans - Temmuz 2005 Belirsizliği, Örgüt Yapısı, Mekanistik ve Organik Sistemler, Örgüte İçten Bağlılık ÖZET Çalışmada asıl olarak, algılanan iş belirsizliği ve örgüte içten bağlılık ilişkisine, örgüt yapısının, algısal olarak ölçülen mekanistik-organik sistem eğiliminin etkisi araştırılmıştır. İş belirsizliği, ölçüm aracı üzerinde yapılan analizler sonucunda, tahlil belirsizliği adlı tek bir faktör ile temsil edilmiştir. Gerek verilerin toplamı üzerinden, gerekse verinin araştırma-geliştirme, satış-pazarlama ve üretim departmanlarına ayrılması suretiyle yapılan analizler sonucunda, mekanistik-organik sistem algısının belirtilen ilişki üzerinde mânidar bir etkisi olmadığı ortaya çıkmıştır. Bununla beraber, algılanan tahlil belirsizliği ve örgüte içten bağlılık ilişkisi üzerinde örgüt yapısı boyutlarından olan güvenin mânidar bir değiştirici etkisi olduğu görülmüştür. Aynı bulgu üretim departmanı için de geçerlidir. Araştırma-geliştirme, satış-pazarlama ve üretim departmanları algıladıkları tahlil belirsizliğine göre yeniden sıraya dizilmiş, sıralama yüksekten düşüğe doğru satış-pazarlama, araştırma-geliştirme ve üretim olarak gerçekleşmiştir. Algılanan tahlil belirsizliğinin, kıdemle negatif ilişkili, eğitimle ise pozitif ilişkili olduğu görülmüştür. Ayrıca, okul dışında işlerinde kendilerine yardımcı olacak herhangi bir eğitim almış olan çalışanların eğitim almayan çalışanlara göre tahlil belirsizliğini daha yüksek algıladığı bulunmuştur. Bahsedilen tüm bulgular araştırmanın sonunda tartışılmıştır.
Keywords: İş Belirsizliği; Mekanistik ve Organik; Örgüt Yapısı; Örgüte İçten Bağlılık; Sistemler